RESPONSE OF TWO VARIETIES OF PECHAY (Brassica rapa) APPLIED WITH DIFFERENT LEVELS OF FERMENTED PLANT JUICE - Luzviminda Obligado Laysa; TARUMA, ARVIN BUEMIA (International Journal of Multidisciplinary Research and Studies, 2023)
This study is an experiment which was conducted from November 2021 to January 2022 at Brgy. Calangay, Santa Maria, Laguna to evaluate the different levels of Fermented Plant Juice (FPJ) on the growth and yield performance of different varieties of pechay in terms of weekly height of the plant, length of leaves, width of leaves, number of leaves, biological yield, economical yield, shoot root ratio, and cost and return. The study laid out in Randomized Complete Block Design (RCBD) to determine the response of different varieties of pechay (Brassica rapa) applied with different levels of Fermented Plant Juice (FPJ). It is a 2 x 5 factorial experiment with the varieties of Pechay as factor A (Pavo and Pavito), and the level of the Fermented Plant Juice (FPJ) as level factor B (control, 15ml. 22.5ml, 30ml, and 37ml, of FPJ/L of water). The experimental treatments were replicated 4 times. The collected data were analyzed with the use of the Statistical Tool for Agriculture Research (STAR) and significant results were subjected to statistical analysis using Least Significant Difference (LSD) Test. The results showed that growth characteristics such as length of leaves, average number of pechay leaves, average width of pechay leaf, biological yield, economic yield, shoot root ratio, and cost and return show significant effects in terms of the FPJ level. Using 37.5ml. of FPJ/litter of water as level of treatment for pechay has significant effect on the growth and yield performance of pechay Pavo. The study recommends the use of 37.5ml. of FPJ/L. of water as level of the FPJ for better results.